Uji Efektivitas Sediaan Salep Ekstrak Daun Kenikir (Cosmos Caudatus Kunth) Terhadap Penyembuhan Luka Sayat Pada Kelinci Jantan New Zealand White - Annissha Azzahra Wurnasari; Kusumaningtyas Siwi Artini; Bangkit Riska Permata (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Kenikir Leaf Extract (Cosmos Caudatus Kunth) is a medicinal plant that can be used to heal cut wounds. This research aims to determine the compound content in kenikir leaves, determine the physical quality and stability of kenikir leaf extract ointment preparations, and determine the effective concentration for healing cuts on the backs of male New Zealand White rabbits. This type of research is experimental, making ointment formulations using kenikir leaf extract made in 3 concentrations, namely 10%, 15% and 20%. In ointment testing, organoleptic tests, homogeneity tests, spreadability tests, adhesion tests, pH and viscosity tests are carried out. Testing the effectiveness of wound healing using 5 groups, namely Betadine ointment (+), ointment base (-), kenikir leaf extract ointment 10%, 15% and 20% on 5 rabbits with a wound length of 1.5 cm was carried out until the 3rd day. 7. The data was processed statistically using One Way ANOVA (Analysis of Variant) and continued with the LSD (Least Significant Difference) test. The results of this research show that kenikir leaf extract ointment 10%, 15% and 20% produces an ointment that meets the requirements of the organoleptic test, homogeneity test, spreadability test, adhesiveness test and pH test, as well as providing healing effects on cuts and wounds in rabbits and The most effective healing power is 20% kenikir leaf extract ointment.